Scanning Probe Microscopy in Nanoscience and Nanotechnology 3 - Bhushan, Bharat; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book presents the physical and technical foundation of the state of the art in applied scanning probe techniques. It constitutes a timely and comprehensive overview of SPM applications. The chapters in this volume relate to scanning probe microscopy techniques, characterization of various materials and structures and typical industrial applications, including topographic and dynamical surface studies of thin-film semiconductors, polymers, paper, ceramics, and magnetic and biological materials. The chapters are written by leading researchers and application scientists from all over the world and from various industries to provide a broader perspective.
Part 1: Scanning probe microscopy techniques- Spectroscopic techniques in SPM- High speed AFM imaging -- New developments in imaging of biological samples -- New developments in AFM -- SNOM -- Part 2: Nanocharacterization -- Antibodies for protein recognition -- In-situ imaging of living cells -- In-situ crystallization of wax materials -- Part 3: Biomimetics and industrial applications -- Electrowetting and switchable hydrophobicity -- Renewable energy applications -- AFMs in hard disk industry.
Keywords: Physics; Engineering; Biomedical engineering; Biomaterials; Nanotechnology; Surfaces (Physics).; Physics; Nanoscale Science and Technology; Nanotechnology; Nanotechnology and Microengineering; Biomedical Engineering; Biomaterials; Characterization and Evaluation of Materials